Phylogenetic Grouping and Virulence Potential of Extended-Spectrum-β-Lactamase-Producing Escherichia coli Strains in Cattle - Valat, Charlotte (American Society for Microbiology, 2012)
In line with recent reports of extended-spectrum beta-lactamases (ESBLs) in Escherichia coli isolates of highly virulent serotypes, such as O104:H4, we investigated the distribution of phylogroups (A, B1, B2, D) and virulence factor (VF)-encoding genes in 204 ESBL-producing E. coli isolates from diarrheic cattle. ESBL genes, VFs, and phylogroups were identified by PCR and a commercial DNA array (Alere, France). ESBL genes belonged mostly to the CTX-M-1 (65.7%) and CTX-M-9 (27.0%) groups, whereas those of the CTX-M-2 and TEM groups were much less represented (3.9% and 3.4%, respectively). One ESBL isolate was stx(1) and eae positive and belonged to a major enterohemorrhagic E. coli (EHEC) serotype (O111:H8). Two other isolates were eae positive but stx negative; one of these had serotype O26:H11. ESBL isolates belonged mainly to phylogroup A (55.4%) and, to lesser extents, to phylogroups D (25.5%) and B1 (15.6%), whereas B2 strains were quasi-absent (1/204). The number of VFs was significantly higher in phylogroup B1 than in phylogroups A (P = 0.04) and D (P = 0.02). Almost all of the VFs detected were found in CTX-M-1 isolates, whereas only 64.3% and 33.3% of them were found in CTX-M-9 and CTX-M-2 isolates, respectively. These results indicated that the widespread dissemination of the bla(CTX-M) genes within the E. coli population from cattle still spared the subpopulation of EHEC/Shiga-toxigenic E. coli (STEC) isolates. In contrast to other reports on non-ESBL-producing isolates from domestic animals, B1 was not the main phylogroup identified. However, B1 was found to be the most virulent phylogroup, suggesting host-specific distribution of virulence determinants among phylogenetic groups.